Guidelines for solid waste management: Overcoming challenges and exploit opportunities - Anuardo, R. G. [UNESP]; Espuny, M. [UNESP]; de, V. [UNESP]; de Oliveira, O. J. [UNESP] (My University, 2021)
Approximately one million people die each year in the world because of chemical contamination caused by solid waste disposal. From 1991 to 2000, the amount of solid waste produced in the world was 0.68 billion tons, from 2010 to 2018 it increased to 1.3 billion tons, and it is estimated that by 2025 it will be 2.2 billion tons. Solid waste includes food waste, paper, plastics, glass, textiles, metals, wood, leather, and others; and is produced in human activities, both in households and organizations, and requires handling, storage, collection, and disposal. The main challenges identified in the literature on solid waste management are difficulty in measuring and controlling environmental and social impacts, lack of legislation applied to waste and of specialized workers, structural and budgetary deficiency, and lack of management-oriented strategies and statistical tools. Within this scenario, the objective of this chapter is to propose recommendations for developing solid waste management based on the identification of scientific opportunities and challenges in the literature. Based on what was identified, benchmarking was performed, and recommendations were proposed to overcome the challenges of solid waste management. The main scientific contribution of this chapter is the deepening and expansion of the literature on solid waste management based on the solutions to the challenges, which will help and stimulate future research on the topic. As for the applied contribution, this work presents suggestions of actions for public managers and entrepreneurs of the solid waste sector with the perspective of process automation, waste destination, sustainability of the planet, and the reduction of waste production.
Keywords: Challenges; Recommendations; Solid waste management; Waste